The influence of patient self-efficacy on value co-creation behavior and outcomes in chronic disease management: a cross-sectional study - Jiamin Tang; Jie Jia; Yuan Gao; Weixiao Yu; ZhengNan Meng; Hailong Zhu; Xianhong Huang (BMC Public Health)
Abstract Background In the medical field, value co-creation involves patients’ active involvement. By collaborating with service providers, patients can contribute to the creation of more targeted and effective value. Patients’ self-efficacy and behavior are crucial in this process, as their active participation and support can enhance their service experience. This study investigated the impact of chronic disease patients’ self-efficacy and value co-creation behaviors on the outcomes of value co-creation. Methods Relevant data were acquired through a questionnaire survey using statistical methods, such as the t-test, analysis of variance, and stratified linear regression. This approach was used to examine the current conditions and factors influencing value co-creation outcomes among community-dwelling patients with chronic diseases. Additionally, a structural equation model was employed to systematically investigate and validate the impact pathways and mechanisms related to the influence of self-efficacy and value co-creation behaviors on value co-creation outcomes. We also explored the moderating effect of digital health technology application capabilities on the relationship between self-efficacy and value co-creation behaviors. Results Self-efficacy, information search, interactive collaboration, feedback provision, and shared decision-making exert significant positive influences on the value co-creation outcomes among individuals with chronic diseases. The path analysis of the structural equation model indicates that self-efficacy and value co-creation behaviors may directly impact value co-creation outcomes. Concurrently, value co-creation behaviors partially mediate the association between self-efficacy and value co-creation outcomes. Furthermore, the digital health technology application capability exhibits a negative moderating effect in the pathway from self-efficacy to value co-creation behaviors. Conclusions The implementation of health education and social support measures by healthcare institutions and communities may augment patient self-efficacy, facilitate doctor-patient interactions, and promote shared decision-making. These initiatives could enhance the value of chronic disease services and optimize patient experiences. Additionally, healthcare institution managers are encouraged to focus on optimizing internet hospital platforms, organizing digital health training for patients, and bolstering patients’ proficiency in digital health technology applications. This strategy aims to instill a sense of health responsibility among patients with chronic diseases by fostering positive behaviors in interactive collaboration, information search, feedback provision, and other dimensions.